A survey of elite and pre-elite athletes` perceptions of key support, lifestyle and performance factors - Burns, L.; Weissensteiner, J. R.; Cohen, M.; Bird, S. R. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Success at the elite level in sport is often attributed to physical prowess, technical skill, and mental attitude. However, underpinning these factors are various lifestyle, support and social factors that may contribute to successful performance, but which may be absent from athlete development programs.